Accelerated reliability testing of articulated cable bend restrictor for offshore wind applications. (December 2016) - Thies, Philipp R.; Johanning, Lars; Bashir, Imran; Tuk, Ton; Tuk, Marloes; Marta, Marco; Müller-Schütze, Sven
Highlights: Full-scale accelerated reliability tests of static submarine marine power cable-bend restrictor specimen subjected to combined axial and bending cycles. Demonstrated integrity of cable protection system with quantified wear rates obtained through 3D scanning. Static submarine power cable exposed to 77k cycles, showing incipient failures (fatigue cracking & fretting) that are described in detail. Observed failure modes are predicted through numerical load analysis, giving confidence in stress analysis methods. Abstract: Power cable failures for offshore marine energy applications are a growing concern since experience from offshore wind has shown repeated failures of inter-array and export cables. These failures may be mitigated by dedicated cable protection systems, such as bend restrictors. This paper presents the rationale and the results for accelerated reliability tests of an articulated bend restrictor. The tests are a collaborative effort between the University of Exeter, CPNL Engineering and NSW, supported by the EU MARINET programme. The tests have been carried out at full-scale and exposed the static submarine power cable, fitted with an articulated pipe bend restrictor, to mechanical load regimes exceeding the allowable design loads in order to provoke accelerated wear and component failures. The tested load cases combined cyclic bending motions with oscillating tensile forces. A range of acceleration factors have been applied in respect to the 1:50 years load case, subjecting each of the three restrictor samples to 25, 000 bending cycles (50, 000 tensile cycles). The static power cable was also loaded beyond its intended use, testing the worst case scenario of repeated dynamic loading, purposely inflicting failure modes for investigation. Throughout the test the static submarine power cable sustained over 77, 000 bending cycles. The test demonstrated the integrity of the cable protection system with quantified wear rates obtained through 3D scanning of the individual shells. The static power cable also maintained its integrity throughout the accelerated test regime. None of the failure modes, mainly fatigue cracks and fretting of individual wires, identified by cable dissection would have caused a direct loss of service. The observed failure modes could also be predicted through numerical load analysis, giving confidence in the utilised mechanical modelling and cross-sectional analysis for dynamic applications.